2014
DOI: 10.1016/j.jmoldx.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Validation for Clinical Use of, and Initial Clinical Experience with, a Novel Approach to Population-Based Carrier Screening using High-Throughput, Next-Generation DNA Sequencing

Abstract: Traditional carrier screening assays are designed to look for only the most common mutations within a gene owing to cost considerations. Although this can yield high detection rates in specific populations for specific genes (such as cystic fibrosis in Caucasians), they are suboptimal for other ethnicities or for patients of mixed or unknown ethnic background. Next-generation DNA sequencing provides an opportunity to provide carrier screening using more comprehensive mutation panels that are limited primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…Overall, 99.39% of 2635 replicate variants were detected in all 3 replicates at a sensitivity of 99.42%, specificity of 99.99%, PPV of 99.86%, and NPV) of 99.94% from 7500 shared interrogations between NGS and array analysis. These frequencies are similar to reproducibility rates of 95.6%-98.8% (21,22 ), sensitivities of 95.9%-99.4% (21,23,24 ), and specificity of 100% (21 ) reported in studies using higher-throughput NGS formats, indicating an equivalence in analytical performance between modes. Notably, 11/16 (69%) replicate variants that were detected inconsistently had allele frequencies Յ0.15, strand biases ϾϪ35, or genotype quality scores Յ80 ( Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, 99.39% of 2635 replicate variants were detected in all 3 replicates at a sensitivity of 99.42%, specificity of 99.99%, PPV of 99.86%, and NPV) of 99.94% from 7500 shared interrogations between NGS and array analysis. These frequencies are similar to reproducibility rates of 95.6%-98.8% (21,22 ), sensitivities of 95.9%-99.4% (21,23,24 ), and specificity of 100% (21 ) reported in studies using higher-throughput NGS formats, indicating an equivalence in analytical performance between modes. Notably, 11/16 (69%) replicate variants that were detected inconsistently had allele frequencies Յ0.15, strand biases ϾϪ35, or genotype quality scores Յ80 ( Fig.…”
Section: Discussionsupporting
confidence: 82%
“…NGS allows for the detection of many more mutations than traditional genotyping‐based carrier screens, while still detecting so‐called common mutations (Hallam et al. 2014; Perreault‐Micale et al. 2014).…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with a recent multiethnic study in which a quarter of the mutations detected by NGS are not included in traditional, limited, mutation panels (Hallam et al. 2014). Our model predicts that, for a large population, NGS will identify 10% or more mutation carriers than traditional genotyping, which is also consistent with the improvements calculated using data from the clinical database of 71,070 patients described in Table S7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach identifies an increased number of carriers and significantly increases sensitivity. Hallam et al have also reported a NGS screening approach 22. Approximately 25% of the mutations they found would not have been detected with traditional targeted genotyping screening panels.…”
Section: Expanded Carrier Screeningmentioning
confidence: 99%